2015
DOI: 10.1371/journal.pone.0128532
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Novel Synthetic Peptides Derived from Indolicidin and Ranalexin against Streptococcus pneumoniae

Abstract: Antimicrobial peptides (AMPs) represent promising alternatives to conventional antibiotics in order to defeat multidrug-resistant bacteria such as Streptococcus pneumoniae. In this study, thirteen antimicrobial peptides were designed based on two natural peptides indolicidin and ranalexin. Our results revealed that four hybrid peptides RN7-IN10, RN7-IN9, RN7-IN8, and RN7-IN6 possess potent antibacterial activity against 30 pneumococcal clinical isolates (MIC 7.81-15.62µg/ml). These four hybrid peptides also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 66 publications
1
63
0
Order By: Relevance
“…The HC 50 /MIC values of linear α-polylysine and all the glycopolymer-polypeptide conjugates are generally higher than those of many other antimicrobial peptides, such as indolicidin, 43 8, 8, 5 and 3, respectively, when calculated using MIC toward S. aureus. The hemoselectivity of P(Lys) and P(GlyEMA) 10 -P(Lys) is even higher than that of polymyxin B, a topical antibiotic with an HC 50 /MIC value of approximately 141 against S. aureus.…”
Section: Antimicrobial Properties Of the Four-arm Star Glycopolymer-pmentioning
confidence: 91%
“…The HC 50 /MIC values of linear α-polylysine and all the glycopolymer-polypeptide conjugates are generally higher than those of many other antimicrobial peptides, such as indolicidin, 43 8, 8, 5 and 3, respectively, when calculated using MIC toward S. aureus. The hemoselectivity of P(Lys) and P(GlyEMA) 10 -P(Lys) is even higher than that of polymyxin B, a topical antibiotic with an HC 50 /MIC value of approximately 141 against S. aureus.…”
Section: Antimicrobial Properties Of the Four-arm Star Glycopolymer-pmentioning
confidence: 91%
“…Although higher net charge, hydrophobicity, helical propensity, and presence of a conserved sequence are able to enhance the antimicrobial activity of AMPs in general, however, these sets of rules do not apply equally to all classes of AMPs. For example, our previous studies showed that the antibacterial activity of five designed AMPs (DM1 to DM5) was correlated to net charge within specific window values (79,174,175). Anionic AMPs have also been documented in the literature (176,177).…”
Section: Important Remarksmentioning
confidence: 95%
“…60 After structures optimization, molecular docking was performed using AutoDock Vina, which is widely used in the interaction analysis of proteins with small molecules. 61,62 The Vina scoring function has the advantage of using the knowledge and empirical functions, extracting information about conformational preferences and the affinity of the receptor-ligand complex based on empirical data. 63 The program generates a maximum of 20 conformations for each complex.…”
Section: Resultsmentioning
confidence: 99%